Understanding the issue of plastic waste pollution in Malaysia: a case for human security / Nur Raudhah Ibrahim and Noor Nirwandy Mat Noordin - Ibrahim, Nur Raudhah; Mat Noordin, Noor Nirwandy (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2020)
The crisis of plastic waste pollution in Malaysia appears to be snowballing at an unmatched rate. It has also been concerning to know that a large portion of plastic waste was never recycled, in addition to containers of illegal Britain's plastic wastes shipped into the country to be dealt with. While the issues of plastic waste pollution in Malaysia surpasses crisis levels, this study centres on gathering information from those who are enthralled in protecting the human survival and livelihood, in their effort to keep the planet clean from plastic waste pollution. Environmental concerns were rarely perceived as a security problem, but now that the concept of human security has transcended beyond its traditional understanding of state security, this research identifies and analyses the ongoing issues with the crisis of plastic waste pollution, and the current approaches being adopted in solving the crisis. Aiming at devising a plan that addresses the root of the problem to catalyze a significant reduction in plastic waste pollution, this study applies a thematic qualitative analysis that can best be used to interpret and analyze the dataset. The findings indicate that economic development, although beneficial, has given birth to capitalist market, that eventually results in eco-economic crisis. The study also points out that a number of efforts has not been influencing the current plastic pollution mitigation in the country. Therefore, this study provides a better understanding of how human security can be factored into the crisis resolution of plastic waste pollution. A realistic transformation towards eco-effective nation holds the key to mitigation efforts.